The effects of degrees of Dutch accentedness in ELF and in French, German and Spanish. (11th February 2015) - Hendriks, Berna; van Meurs, Frank; de Groot, Elizabeth
Abstract : In a verbal guise experiment, 178 listeners with three nationalities (58 French, 59 German and 61 Spanish) listened to samples recorded by female speakers with three degrees of accentedness (strong/slight accented‐Dutch and native) in English, French, German and Spanish. Findings indicate that a strong accent had a detrimental effect on understanding and attitudinal evaluations, while a slight accent hardly led to negative effects. A speaker with a strong Dutch accent in English was evaluated as less competent than speakers with a slight or native accent. Speakers with a strong Dutch accent in French, German or Spanish were evaluated as less friendly and less competent than speakers with a native accent.